Clinical outcomes of atrial fibrillation with hyperthyroidism. Issue 4 (7th July 2021) - Zubair Khan, Muhammad; Gupta, Ashwani; Hodge, Jordesha; Patel, Kirtenkumar; Patel, Krunalkumar; Zarak, Muhammad Samsoor; Franklin, Sona; Patel, Harsh; Jesani, Shruti; Savani, Sejal; Shah, Vraj; Figueredo, Vincent M.; et al.
Abstract: Background: Atrial fibrillation (Afib) is a common cardiac manifestation of hyperthyroidism. The data regarding outcomes of Afib with and without hyperthyroidism are lacking. Hypothesis: We hypothesized that patients with Afib and hyperthyroidism have better clinical outcomes, compared with Afib patients without hyperthyroidism. Methods: We queried the National Inpatient Sample database for years 2015‐2017 using Validated ICD‐10‐CM codes for Afib and hyperthyroidism. Patients were separated into two groups, Afib with hyperthyroidism and without hyperthyroidism. Results: The study was conducted with 68 095 278 patients. A total of 9 727 295 Afib patients were identified, 90 635 (0.9%) had hyperthyroidism. The prevalence of hyperthyroidism was higher in patients with Afib (0.9% vs 0.4%, P  < .001), compared with patients without Afib. Using multivariate regression analysis adjusting for various confounding factors, the odds ratio of Afib with hyperthyroidism was 2.08 (CI 2.07‐2.10; P  < .0001). Afib patients with hyperthyroidism were younger (71 vs 75 years, P  < .0001) and more likely to be female (64% vs 47%; P  < .0001) as compared with Afib patients without hyperthyroidism. Afib patients with hyperthyroidism had lower prevalence of CAD (36% vs 44%, P  < .0001), cardiomyopathy (24.1% vs 25.9%, P  < .0001), valvular disease (6.9% vs 7.4%, P  < .0001), hypertension (60.7% vs 64.4%, P  < .0001), diabetes mellitus (29% vs 32%, P  < .0001) and obstructive sleep apnea (10.5% vs 12.2%, P  < .0001). Afib with hyperthyroidism had lower hospitalization cost ($14 968 ± 21 871 vs $15 955 ± 22 233, P  < .0001), shorter mean length of stay (5.7 ± 6.6 vs 5.9 ± 6.6 days, P  < .0001) and lower in‐hospital mortality (3.3% vs 4.8%, P  < .0001. The disposition to home was higher in Afib with hyperthyroidism patients (51% vs 42; P  < .0001). Conclusion: Hyperthyroidism is associated with Afib in both univariate and multivariate analysis. Afib patients with hyperthyroidism have better clinical outcomes, compared with Afib patients without hyperthyroidism. Abstract : Atrial fibrillation (Afib) is a common cardiac manifestation of hyperthyroidism. The data regarding clinical outcomes of Afib with and without hyperthyroidism are lacking.